A comprehensive study of oxidative stress in patients with somatic symptom disorder. Issue 2 (18th December 2018) - Kabadayi Sahin, Esra; Caykoylu, Ali; Senat, Almila; Erel, Ozcan
Abstract: Objective: To investigate oxidative stress parameters [total oxidant status (TOS), total antioxidant status (TAS), oxidative stress index (OSI), paraoxonase (PON), arylesterase (ARE) and thiol-disulphide homeostasis] in patients who were diagnosed as having somatic symptom disorder in accordance with Diagnostic and Statistical Manual of Mental Disorders-5. Methods: The study included 41 medication-free patients with somatic symptom disorder and 47 age, sex, and sociodemographic-matched healthy individuals. The patients were administered the Patient Health Questionnaire-15, Somatic Symptom Amplification Scale, Beck Depression Inventory, and Beck Anxiety Inventory. TOS, TAS, OSI, PON, ARE thiol, disulphide levels, and routine biochemical parameters were compared between the two groups. Results: TOS, OSI, disulphide levels, disulphide/native thiol, and disulphide/total thiol ratios were found significantly higher in the patient group compared with the control group ( p < 0.001). There was no significant difference in PON, ARE, and TAS parameters between the two groups ( p > 0.05). Conclusion: This study showed that the level of oxidants increased and oxidative balance was impaired in somatic symptom disorder. Oxidative stress may play a role in the aetiopathogenesis of this disorder. This is the first study to report an association between oxidative stress and somatic symptom disorder.